2018
DOI: 10.1111/jir.12566
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of early cognition in infants with Down syndrome

Abstract: Background While delays in cognitive development are detectable during early development in Down syndrome, the neuropsychological and biomedical underpinnings of cognitive skill acquisition in this population remain poorly understood. Method To explore this issue, 38 infants with Down syndrome [mean chronological age = 9.65 months; SD = 3.64] completed the Bayley Scales of Infant Development‐III and a set of laboratory tasks that measured sustained attention (duration of visual attention during a 1‐min object … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…Although this is the first study to report longitudinal connections between infant attention shifting and early EF in DS, it is not the first to identify attention regulation as an essential developmental skill in this population. A previous study composed of a subsample of participants in the present study reported a significant concurrent relationship between attention shifting and overall cognitive skill acquisition in infants with DS (Fidler et al 2019b). The current study extends these findings and reports longitudinal associations between early attention shifting skills and later cognitive flexibility, inhibition and working memory skills.…”
Section: Attention Regulation Replicationsupporting
confidence: 85%
See 2 more Smart Citations
“…Although this is the first study to report longitudinal connections between infant attention shifting and early EF in DS, it is not the first to identify attention regulation as an essential developmental skill in this population. A previous study composed of a subsample of participants in the present study reported a significant concurrent relationship between attention shifting and overall cognitive skill acquisition in infants with DS (Fidler et al 2019b). The current study extends these findings and reports longitudinal associations between early attention shifting skills and later cognitive flexibility, inhibition and working memory skills.…”
Section: Attention Regulation Replicationsupporting
confidence: 85%
“…In a separate study, faster mean attention shifting latencies were correlated with overall cognitive skill acquisition (Fidler et al . 2019b). Visual engagement and attention shifting difficulties during this early developmental period in DS may have critical downstream implications for EF skill development, but there is no existing longitudinal work to support this link in infants with DS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination of this association should also incorporate additional factors such as prematurity, congenital heart disease (CHD), and parent education level, each of which may impact social communication. Prematurity and CHD are common in DS [35,36] and parent education level has been connected to language outcomes in typically developing children [37].…”
Section: Discussionmentioning
confidence: 99%
“…Another issue concerns when individuals with DS reach certain developmental milestones, and their developmental trajectories can be charted vis-à-vis their acquisition of earlier stages of development. It has been demonstrated that the delay with which individuals with DS reach these milestones is linked to their subsequent cognitive and language development e.g., 34 37 . Motor milestones have been found related to subsequent cognitive and language development 37 , and communication milestones to language development 36 .…”
Section: Introductionmentioning
confidence: 99%